Interactional Styles Used by Team Leader in The Six Key Moments GitLab’s Product Marketing Meeting - Firda Nur Firgiyanti (Kata Kita: Journal of Language, Literature, and Teaching, 2025)
This study aims to find the types of interactional styles that are often used in six key moments by Sid as a team leader when talking to employees on the GitLab YouTube entitled Product Marketing Meeting (Weekly) 2021-06-28. The writer uses a qualitative approach by using Holmes' (2006) main theory of interactional styles and supporting theory of Holmes (2013) of status scale.  In this study, Sid’s utterances in the use of interactional style at six key moments show that Sid uses indirect, collaborative, referentially oriented, facilitative, and task or outcome-oriented. Based on the findings of Sid’s utterances, it uses six feminine interactional styles for building relationships and encouraging team engagement, and three masculine interactional styles for task completion and to ensure clarity. This shows that Sid often uses more feminine interactional styles than masculine interactional styles, even though he is a team leader.